The use of biomarkers in neuroendocrine tumours. Issue 3 (21st March 2013) - Khan, Mohid Shakil; Caplin, Martyn E
Abstract : The incidence and prevalence of neuroendocrine tumours (NETs) arising from the gastrointestinal tract are increasing. At the time of diagnosis, histological grade, based on Ki-67 proliferation index on a tumour biopsy or specimen, offers prognostication but with often lengthy survival, this may not reflect current tumour biology later in the disease course. Biomarkers, including plasma chromogranin A, urinary 5-hydroxyindole acetic acid and pancreatic specific hormones (insulin, gastrin, vasoactive intestinal peptide), have a role in diagnosis but despite being incorporated into routine clinical practice, there is a lack of robust prospectively collected data investigating their prognostic and predictive value. Given the increasing number of treatment options available for NETs and prolonged survival, there is no agreement on the order of treatment for individual NET patients but the emergence of novel biomarkers and validation of existing ones, in addition to better understanding of the molecular biology, may help solve this clinical problem.